The Elusiveness of Welfare-State Specificity - Tahl Kaminer (Footprint)
Review of Architecture and the Welfare State, edited by Mark Swenarton, Tom Avermaete and Dirk van den Heuvel (Oxon and New York: Routledge, 2015).